Evaluating Jordan's antimicrobial resistance national action plan (2018–2022) implementation: progress and recommendations - Salam Momani; Mohammad S. Alyahya; Dalia K. Zayed; Ala Bin Tarif; Omar F. Nimri; Sami Alshaikh; Adel Belbiesi; Ala’a B. Al-Tammemi (BMC Public Health)
Abstract Background Antimicrobial resistance (AMR) is a pressing global public health challenge that requires coordinated multi-sectoral responses under the One Health framework. In line with the Global Action Plan (GAP) on AMR, Jordan developed its first National Action Plan (NAP) for 2018–2022 to guide national efforts. This study aimed to evaluate the implementation of Jordan’s AMR NAP 2018-2022, identify progress and challenges across its five strategic objectives, and suggest actionable recommendations for strengthening future AMR responses. Methods A comprehensive end-term evaluation was conducted for the NAP 2018–2022 by the Jordan Center for Disease Control (Jordan CDC), utilizing a structured evaluation tool including sector-specific and multi-sectoral indicators aligned with the five objectives of the AMR NAP. Data were collected via national stakeholder workshop and follow-up electronic communications, with consensus-based completion by multi-sectoral working groups. Descriptive analysis was used to assess implementation across human, animal, food and environmental sectors, applying the One Health approach. Results The evaluation revealed uneven implementation across sectors and NAP objectives, with notable achievements in the rational use of antimicrobials (69%), mainly in the human health sector, followed by infection prevention and control (IPC) efforts (63%), and surveillance-related activities (56%). Lower progress was reported for awareness activities (47%), while research and innovation activities were not implemented during 2018-2022. Although human health sector activities dominated, gaps persisted across the animal, food, and environmental sectors. Limited intersectoral coordination, the absence of a unified communication strategy, lack of dedicated funding, insufficient investment in human resources and laboratories, and the disruptions caused by the Coronavirus Disease 2019 (COVID-19) pandemic further constrained implementation. The findings underscore critical gaps in One Health surveillance integration, rational antimicrobial use in the food chain, and the need for robust AMR research governance. Conclusions Despite progress in different areas, the overall implementation revealed significant challenges, particularly in research, multi-sectoral collaboration, and the One Health integration. Future action should prioritize a unified national AMR policy framework for strategic planning, emphasizing resource distribution, active participation of all relevant sectors, and institutionalizing systematic monitoring and evaluation to inform policymaking. Strengthening coordination between human, animal, and environmental sectors is essential to achieving a robust, One Health-aligned AMR response in Jordan.